The Effectiveness of Using Video in Teaching Speaking of the Seventh Grade Students’ at SMP Negeri 17 Makassar - Lutfi Jasman; Sujarwo; Suharti Siradjuddin (CV. Eureka Murakabi Abadi, 2023)
Technological developments are also growing rapidly. Its development is almost sectoral, economic, political, and educational have implemented technology. One of them is the use of video. Video can be used as a solution to overcome the low ability of students to understand a concept. This study aims to determine the effect of WhatsApp groups on the ability to write narrative texts of eighth grade students of SMP Negeri 17 Makassar. This study uses a quantitative type of experimental method, there are two classes, namely the experimental class using video and the control class not using video. The sample of this study was class VII students consisting of 32 students for the experimental class and 32 students for the control class. The data collection technique in this study uses pre-test and post-test to collect data by giving text to write. The results of this study indicate that the post-test experimental class has a mean value of 74.69 and the post-test control class has a mean value of 72 ,66. The results of the data analyzed using independent sample t-test, showed that Sig.(2-tailed) was 0.000 lower than 0.05 so that the alternative hypothesis (Ha) was accepted and the null hypothesis (H0) was rejected so that there was an effect of using video in teaching speaking to students after using the video. Based on the results of this study, it can be concluded that video media is effective in improving the speaking ability of seventh grade students of SMP Negeri 17 Makassar.